2021
DOI: 10.1039/d1dt01247a
|View full text |Cite
|
Sign up to set email alerts
|

Two new polyoxometalate-based metal–organic complexes for the detection of trace Cr(vi) and their capacitor performance

Abstract: Two new Keggin-type POM-based metal–organic complexes with different structures have been synthesized, which can be used as electrochemical sensors for the detection of trace Cr(vi) and as supercapacitor materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Additionally, Cr­(VI) ion has been considered as one of the most toxic contaminants due to its high carcinogenicity, which makes it necessary to find an efficient method for detecting Cr­(VI) with low limits of detection. Depending on their redox activity and stability, POM-based complexes have been employed as the electrocatalysts and electrochemical sensors for sensing hydrogen dioxide and nitrite. , In addition, many of the POM-based complexes assembled from different organic ligands such as 2,2′-dimethyl-4,4′-bithiazole, 1,4-bis­(1,2,4-triazol-1-methyl)­cyclohexane, N , N ′-bis­(4-pyrimidinecarboxamido)-1,2-ethane, and 2-aminopyridine exhibit better electrocatalytic activity for detecting Cr­(VI). These works represent potential and cheap ways to detect Cr­(VI) in comparison with noble-metal electrocatalysts. Continuing to develop the POM-based complex is greatly important for exploiting efficient electrochemical materials as sensors, but it can be easily found that those organic ligands involved in the POM-based complexes mentioned above as electrode materials are almost all prefabricated, which interferes with the further development of such POM-based hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Cr­(VI) ion has been considered as one of the most toxic contaminants due to its high carcinogenicity, which makes it necessary to find an efficient method for detecting Cr­(VI) with low limits of detection. Depending on their redox activity and stability, POM-based complexes have been employed as the electrocatalysts and electrochemical sensors for sensing hydrogen dioxide and nitrite. , In addition, many of the POM-based complexes assembled from different organic ligands such as 2,2′-dimethyl-4,4′-bithiazole, 1,4-bis­(1,2,4-triazol-1-methyl)­cyclohexane, N , N ′-bis­(4-pyrimidinecarboxamido)-1,2-ethane, and 2-aminopyridine exhibit better electrocatalytic activity for detecting Cr­(VI). These works represent potential and cheap ways to detect Cr­(VI) in comparison with noble-metal electrocatalysts. Continuing to develop the POM-based complex is greatly important for exploiting efficient electrochemical materials as sensors, but it can be easily found that those organic ligands involved in the POM-based complexes mentioned above as electrode materials are almost all prefabricated, which interferes with the further development of such POM-based hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the electrochemical performances of 1-CPE and 2-CPE for CrIJVI) ion detection exceed those of most of the reported POM-based electrochemical sensors and are comparable to the reported electrochemical sensors containing noble metals (Table 2). 12,33,34,[37][38][39][40] Selectivity, stability, and practicability of 1-CPE and 2-CPE Considering the complexity of the actual aqueous solution, an anti-interference experiment was carried out to verify the stability of the 1-CPE and 2-CPE. A series of metal ions, such as (250 μM) Al 3+ , Zn 2+ , Ni 2+ , Cd 2+ , Cr 3+ , Mn 2+ , Co 2+ , and La 3+ , were chosen as interfering agents.…”
Section: Electrocatalytic and Electrochemical Sensing Propertiesmentioning
confidence: 99%
“…26,27 The synergistic effect of POM and MOFs enables POMOFs to combine the outstanding redox traits of POMs and the multichannel structure of MOFs, which will provide more active centers. 28,29 So there is great potential for POMOFs to be applied in the fields of electrochemistry and catalysis. 30,31 Moreover, the poor conductivity and chemical stability of MOFs also limit their wide application, but POMOFs synthesized by a hydrothermal method can maintain stability in a water environment.…”
Section: Introductionmentioning
confidence: 99%